Pengaruh Kompensasi dan Beban Kerja terhadap Kinerja Karyawan (Studi pada PT. Dipa Puspa Labsains Jakarta Selatan) - Ramadhan, Vicky; Sunarsi, Denok (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2024)
The aim of this research is to determine the effect of compensation and workload on the performance of PT Dipa Puspa Labsains South Jakarta employees, both partially and simultaneously. The method used is quantitative. The sampling technique used the Slovin formula and a sample of 99 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research show that partially there is a positive and significant influence between compensation on employee performance with the simple linear regression equation Y= 24.957 + 0.367X1. The correlation value is 0.576 and the tcount value is 6.948 > ttable 1.985 with a significance of 0.000 <0.05. Partially there is a positive and significant influence between workload on employee performance with the simple linear regression equation Y = 15.317 + 0.602X2. The correlation value is 0.536 and the tcount value is 6.259 > ttable 1.985 with a significance of 0.000 <0.05. Simultaneously there is a positive and significant influence between compensation and workload on employee performance with the multiple linear regression equation Y = 16.210 + 0.253X1 + 0.332X2. The coefficient of determination value is 62.3%. And the Fcount value is 30.428 > Ftable 3.09 with a significance level of 0.000 < 0.05.